Resilience to economic shocks and the long reach of childhood bullying - Nattavudh Powdthavee (Institute for the Study of Labor (IZA), 2012)
This paper investigates whether people's ability to withstand and adapt to one of the most important economic shocks - job loss - is determined early on in childhood. Using nationally representative longitudinal data that tracks almost 3,000 children into adulthood, we show that the negative effect of unemployment on mental health and life satisfaction is almost four times larger for workers who had been bullied a lot in their early life. We also find zero adaptation to unemployment for these individuals over time. Although the results should be viewed as illustrative and more research is needed, their potential implications for economists and policy makers are discussed.
Keywords: D03; I19; J64; 330; resilience; adaptation; happiness; unemployment; childhood; well-being; Arbeitslosigkeit; Persönlichkeitspsychologie; Zufriedenheit; Erwachsene; Kinder; Schätzung; Großbritannien